2012
DOI: 10.1007/s00430-012-0233-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of viral load in infants hospitalized with bronchiolitis caused by respiratory syncytial virus

Abstract: The relationship between viral load, disease severity and antiviral immune activation in infants suffering from respiratory syncytial virus (RSV)-associated bronchiolitis has not been well identified. The main objective of this study was to determine the existence of a correlation between RSV load and disease severity and also between different clinical markers and mRNA levels of the interferon stimulated gene (ISG)56 in infants hospitalized for bronchiolitis. We also evaluated whether viral load tended to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 36 publications
3
52
1
4
Order By: Relevance
“…In the latter study, sample quality was not measured and therefore could not be corrected by RNase P copy number. Additionally, samples were collected from hospitalized infants only and later into the course of infection compared to the current study [17] Others have reported similar associations between viral load and disease severity, but the associations are weak and come either from hospitalized infants [2023] or infants healthy enough to stay home [19, 24]–rarely both [26]. Additionally, most of the samples were collected later in the course of infection than those analyzed here.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter study, sample quality was not measured and therefore could not be corrected by RNase P copy number. Additionally, samples were collected from hospitalized infants only and later into the course of infection compared to the current study [17] Others have reported similar associations between viral load and disease severity, but the associations are weak and come either from hospitalized infants [2023] or infants healthy enough to stay home [19, 24]–rarely both [26]. Additionally, most of the samples were collected later in the course of infection than those analyzed here.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of protective antibodies at the site of infection in young infants with bronchiolitis favours viral replication, leading to high RSV viral load, a factor that has been shown to correlate positively with the clinical severity of the disease and the length of hospital stay [34]. Viral replication directly increases the number of infected cells and, therefore, the extension of the damage to the airway.…”
Section: Rsv and Respiratory Infectionsmentioning
confidence: 99%
“…Importantly, the two are not independent variables. A high viral load has been associated with high release of pro-inflammatory immune mediators and more severe symptoms 1923 . Thus, it is possible that the development of severe disease is due to an early lack of control of the virus, which leads to epithelial cell damage and a high release of pro-inflammatory mediators that recruit and activate leukocytes in the lung and induce an excessive immune response that results in immunopathology 20, 2426 .…”
Section: Rsv Infectionmentioning
confidence: 99%